Effects of spiritual intelligence from Islamic perspective on emotional intelligence - Md. Aftab, Anwar; Osman-Gani, AAhad M.; Rahman, Muhammad Sabbir (Emerald Publishing Limited, 2020)
Purpose – The aim of this study is to develop a spiritual intelligence scale from an Islamic perspective. In addition, this research explores the relationship of spiritual intelligence from an Islamic perspective with emotional intelligence among the students of higher learning institutions in Malaysia. Design/methodology/approach – Data were collected from 250 students from different higher learning institutions in Malaysia. Findings – The findings of the study show the relationships of spiritual intelligence from an Islamic perspective and emotional intelligence. Statistically significant relationships were found between four dimensions of spiritual intelligence from an Islamic perspective (e.g. transcendental awareness, meaning of life, patience and forgiveness) and emotional intelligence. Originality/value – The contribution of human intelligence in the development higher learning institution is remarkable. Most research found on spiritual intelligence is from traditional and Western perspective with very limited studies found from an Islamic perspective. The purpose of the current study is to construct a spiritual intelligence from an Islamic perspective and empirically validate the items. The study also looks for relationships of spiritual intelligence from an Islamic perspective and emotional intelligence among the students of higher learning institutions.